Antifungal Activity of Tamarind (TamarindusindicaLinn.) Leaf Extract Against Colletotrichum gloeosporioides - Jonnalexer B. David; Mary Grace B. Gatan (Philippine Association of Institutions for Research, Inc., 2013)
Anthracnose (Colletotrichum gloeosporioides) is considered as most important and destructive disease of mango. Use of natural plants is recommended because it is cost-effective and safe. Plant extracts like tamarind shown  to have antifungal activity. The experiment was conducted in Pampanga, Philippines following two factor-factorial Complete Randomized Design to determine the antifungal effect of tamarind against anthracnose, specifically to: determine zones of inhibition in C. gloeosporioides as affected by different solvents in young and mature leaf extracts; determine interaction effect between different solvents and type of leaf used; determine the most effective tamarind extract against C. gloeosporioides. Results reveals that young tamarind leaf extract at 1:1 ratio significantly affected the production of zone of inhibition of C. gloeosporioides while the mature tamarind leaf extract did not inhibit the test organism. The ethanol extract using young leaves were the most effective against the test organisms. Findings showed that the use of young tamarind leaf extract using different solvents at 1:2 ratio produced strong effect against anthracnose in terms of inhibitory activity. The use of young leaf ethanol extract against anthracnose was effective and can be considered as good biofungicide because its efficacy is comparable to Mancozeb.